2020
DOI: 10.1371/journal.pntd.0008148
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of plasma cell-free Echinococcus spp. DNA in echinococcosis patients using ultra-high-throughput sequencing

Abstract: Background Echinococcosis is a life-threatening parasitic disease caused by Echinococcus spp. tapeworms with over one million people affected globally at any time. The Echinococcus spp. tapeworms in the human body release DNA to the circulatory system, which can be a biomarker for echinococcosis. Cell-free DNA (cfDNA) is widely used in medical research and has been applied in various clinical settings. As for echinococcosis, several PCR-based tests had been trialed to detect cell-free Echinococcus spp. DNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
0
22
0
1
Order By: Relevance
“…Moradi et al concluded that their method of targeting long fragments could have missed the target as Echinococcus probably releases shorter fragments of cfDNA (90-200 bp) into the blood circulation [8]. Another study indeed found that the E. granulosus cfDNA in CE patients' plasma was mainly 100-350 bp, and that the E. multilocularis cfDNA in AE patients' plasma had a peak of 135 bp (50-330 bp), showing that the Echinococcus cfDNA in echinococcosis patients' blood occurs in shorter fragments [10].…”
Section: Echinococcus Cfdna In Echinococcosis Patients' Bloodan Updatementioning
confidence: 98%
See 4 more Smart Citations
“…Moradi et al concluded that their method of targeting long fragments could have missed the target as Echinococcus probably releases shorter fragments of cfDNA (90-200 bp) into the blood circulation [8]. Another study indeed found that the E. granulosus cfDNA in CE patients' plasma was mainly 100-350 bp, and that the E. multilocularis cfDNA in AE patients' plasma had a peak of 135 bp (50-330 bp), showing that the Echinococcus cfDNA in echinococcosis patients' blood occurs in shorter fragments [10].…”
Section: Echinococcus Cfdna In Echinococcosis Patients' Bloodan Updatementioning
confidence: 98%
“…However, this conclusion was based on one paper [6]. In recent years there have been several publications on the detection of Echinococcus cfDNA in the samples of echinococcosis patients (Table 1) [7][8][9][10][11][12][13].…”
Section: Echinococcus Cfdna As a Potential Diagnostic Tool For Human Echinococcosismentioning
confidence: 99%
See 3 more Smart Citations